Limnebius acupunctus, a new species of water beetle from Australia and Papua New Guinea (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2004)
Limnebius acupunctus, new species, is described, based on a study of 2,013 specimens. This is the first species of the genus to be described from Australia and Papua New Guinea. The wide geographical distribution of the species is mapped, together with illustrations of aedeagal variation. High resolution digital images of the holotype are presented.